Sequential antibody induction for immune tolerance in clinical organ transplantation: a feasibility review of immunosuppressant withdrawal protocols - Yachao Li; Fuxia Chen; Xia He; Lian Yan; Anzhu Bao (Frontiers in Immunology, 2026)
Long-term immunosuppressant use after solid organ transplantation causes serious complications, including chronic rejection, infection, malignancy, and metabolic disorders, which has motivated the clinical pursuit of immune tolerance induction. Sequential antibody induction protocols – using peri-transplant antibodies (e.g., alemtuzumab, anti-thymocyte globulin, belatacept, anti-CD40 monoclonal antibodies) combined with phased reduction or withdrawal of maintenance drugs – aim to establish “operational tolerance” or complete tolerance. This review systematically examines the immunological rationale and major clinical strategies (T-cell depletion, costimulation blockade, mixed chimerism, and regulatory cell therapy). Based on efficacy, safety, and feasibility, we propose four novel sequential regimens with explicit evidence levels. Our multidimensional feasibility assessment – covering cost, complexity, risk–benefit, patient selection, and regulatory barriers – indicates that costimulation-blockade protocols currently offer the best balance for near-term clinical use, whereas chimerism approaches are the most effective but remain restricted to specialised centres. Future work should integrate precise immune stratification, advanced antibody engineering, and cell-based therapies to facilitate individualized sequential protocols, ultimately moving the field from lifelong immunosuppression to controlled immune tolerance.